2021
DOI: 10.1186/s40902-021-00310-w
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with osteonecrosis of the jaw with oral versus intravenous bisphosphonate treatment

Abstract: Purpose This retrospective study was aimed to evaluate the clinical characteristics and treatment outcomes in patients with osteonecrosis of the jaw who were receiving oral versus intravenous (IV) bisphosphonate (BP). Materials and methods This retrospective study enrolled subjects who had been diagnosed with medication-related osteonecrosis of the jaw (MRONJ) during the period from July 2010 to June 2014. Information regarding the following demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…7,8,10 It has been suggested that MRONJ is less aggressive with smaller extent of lesion when oral bisphosphonates are used as compared intravenous counterparts, potentially yielding better global quality of life scores. 25,26 Within our cohort, we found a signi cant correlation between global health status of the patients and drugs linked to MRONJ as well as the route of administration. Cancer patients with MRONJ, who received zoledronic acid had lowest global health status scores.…”
Section: Discussionmentioning
confidence: 65%
“…7,8,10 It has been suggested that MRONJ is less aggressive with smaller extent of lesion when oral bisphosphonates are used as compared intravenous counterparts, potentially yielding better global quality of life scores. 25,26 Within our cohort, we found a signi cant correlation between global health status of the patients and drugs linked to MRONJ as well as the route of administration. Cancer patients with MRONJ, who received zoledronic acid had lowest global health status scores.…”
Section: Discussionmentioning
confidence: 65%
“…McGowan K et al, Premoli A et al, Kaibuchia N et al, Lee S, affirm that the location with the greatest tendency to develop MRONJ is the mandible in the posterior sector, specifically in the molar area, which could be attributed to the decreased vascularity of the mandible (13) (33) (44) (48). However, Falinda et al, determined that the region with the greatest involvement of MRONJ was the maxilla, contrasting with the information expressed in previous studies.…”
Section: Discussionmentioning
confidence: 98%

Medication-related osteonecrosis: Literature review

Idrovo Campoverde María Coralía,
Bacuilima Ñauta Erika Susana,
Pesántez Alvarado Juan Martín
et al. 2023
World J. Adv. Res. Rev.
“…A study in 2012, which evaluated patients with cancer and MRONJ, showed that inflammatory dental diseases were a risk factor in 50% of the cases [36]. On the other hand, the administration of IV bisphosphonates could cause a greater degree of inflammation as a result of their ability to inhibit bone remodeling [56]. However, since a common treatment of inflammatory dental disease is dental extraction, pre-existing dental disease may confuse the relationship between dental extraction and the risk for MRONJ.…”
Section: Discussionmentioning
confidence: 99%